THE RELATIONS OF SMOKER STATUS TOWARDS OXYGEN SATURATION OF INTRA OPERATIONS WITH GENERAL INHALATION IN RSUD DR. SOEDIRMAN KEBUMEN - SERA ADHE ANANTIGAS TIMOR; Jenita Dolu Tine Donsu; Sri Hendarsih (Poltekkes Kemenkes Yogyakarta, 2021)
The impact that can occur in patients with smoker status is decreased oxygen saturation in the bloodstream, this will affect the anesthesia and surgery because the conditions for surgery are hemodynamically stable, including oxygen saturation. This study aims to determine the status of smokers on oxygen saturation in intra-operative patients with general inhalation anesthesia in Dr. Sudirman Kebumen. This research is a non-experimental research with a cross sectional study design. The population in this study were all patients who would undergo surgery with general inhalation anesthesia in Dr. Sudirman Kebumen, the samples in this study were taken by consecutive sampling 60 samples. Data analysis using Chi square test. The results of the study have been obtained respondents with smoker status there are 25 people (41.7%) with saturation <95% and 5 people (8.3%) with oxygen saturation ?95, respondents with non-smoker status obtained results of 4 people (41 , 7%) with oxygen saturation <95 and 26 people (43.3%) with oxygen saturation ?95%. From the researsh, it can be concluded from the results of the study that there is a significant relationship between smoker status and intraoperative oxygen saturation. Dampak yang dapat terjadi pada pasien dengan status perokok adalah menurunya saturasi oksigen dalam aliran darah, hal ini akan berpengaruh dalam proses anastesi dan pembedahan karena syarat tindakan operasi adalah hemodinamik yang stabil, termasuk saturasi oksigen. Penelitian ini bertujuan untuk mengetahui status perokok terhadap saturasi oksigen pada pasien intra operasi dengan general anastesi inhalasi di RSUD Dr. Soedirman Kebumen. Penelitian ini merupakan penelitian non eksperimen dengan desain penelitian potong lintang (Cross Sectional). Populasi dalam penelitian ini adalah semua pasien yang akan menjalani operasi dengan tindakan general anestesi inhalasi di RSUD Dr. Soedirman Kebumen, sampel dalam penelitian ini diambil dengan cara consecutive sampling 60 sampel. Analisa data menggunakan uji Chi square. Hasil penelitian yang telah dilakukan diperoleh responden dengan status perokok terdapat 25 orang (41,7%) dengan saturasi <95% dan 5 orang (8,3%) dengan saturasi oksigen ?95, responden dengan status bukan perokok diperoleh hasil 4 orang (41,7%) dengan saturasi oksigen <95 dan 26 orang (43,3%) dengan saturasi oksigen ?95%. Dapat disimpulkan dari hasil penelitian terdapat hubungan yang signifikan antara status perokok terhadap saturasi oksigen intra operasi